Mediating effect of job satisfaction on Human Resources Management practices and school teachers' operational performance - Uddin, Mohammad Jamal; Rahman, Mohammad Mizanur; Abdul, Mohani; Mansor, Zuraina (Science Publishing Corporation, 2019)
The objectives of this paper are to predict the operational performance of secondary school teachers’ based on Human Resources Management (HRM) practices and to find out the mediating effect of job satisfaction on the relationship between HRM practices and operational performance effort. Cross-sectional survey research design has been used and a structured self-administered survey questionnaire used to collect from 140 teachers at 14 high schools located in Bangladesh. Different statistical measures such as descriptive statistics, Karl Pearson’s correlation, Ordinary Least Square (OLS) multiple regression analysis were used to explore research observations and statistical verification of findings. Apart from these statistical measures, a single mediation model has been tested to know the mediating effect of job satisfaction on the relationship between HRM practices and operational performance effort. Consistent with hypotheses, empirical findings revealed that HRM practices significantly predicted high school teachers’ performance effort. Training & development, discipline and compensation are significantly related to operational performance and they have both direct and indirect effects (through the mediator) on operational performance effort. Implications for institutions and practitioners practicing HRM policies and future research have also discussed.